Transcendent Moments at Work: Breaking Through the Boundaries of Professionalism - Franck, Henrika (Journal of management, spirituality & religion, 2026)
Professionalism provides structure and fairness but often discourages emotional openness, limiting recognition and ethical connection at work. This article explores how professionals move through, and at times beyond, these constraints to experience transcendent moments ‐ episodes of mutual recognition that suspend formal roles and enable authentic interpersonal connection. Drawing on Axel Honneth’s theory of recognition, we distinguish between ethical agency (value-driven moral courage) and spiritual agency (openness to transcendent connection and meaning) and show how their intersection enables transcendent moments. Using qualitative data from interviews, reflective diaries, and testimonials of middle managers, Executive MBA students, and undergraduates, we identify how professionals navigate tensions between detachment and vulnerability. Our findings highlight the role of inner struggle, relational risk, and mutual recognition in enabling these moments. The study advances workplace spirituality theory by framing transcendence as an embodied, relational achievement rather than an institutional program, and extends recognition theory by conceptualizing mutual recognition of vulnerability as a work-specific form of affective recognition.